Cultivating Entrepreneurial Mindsets Among Culinary Arts Diploma Students - Amalia, Intan Fauzia; Yusuf, Maryam; Zaenal, Faisal Akbar (Journal of Economic Education and Entrepreneurship Studies, 2024)
This study examines the entrepreneurial intentions and readiness of students enrolled in the Culinary Arts Diploma Program at Politeknik Pariwisata Makassar. The research employed a qualitative approach using semi-structured interviews with 37 students from different cohorts (2022-2024) to explore their perspectives on starting culinary businesses, their perceived readiness, and the support they need. The findings reveal a strong entrepreneurial interest, with 78% of students eager to start businesses, especially restaurants or cafés. Additionally, 60% of students have prior culinary work experience, demonstrating a solid foundation for entrepreneurship. However, while 59.46% feel moderately prepared, 21.62% report feeling underprepared to face business challenges. The study identifies critical gaps, including the need for enhanced entrepreneurship training, greater access to financial resources, and increased industry exposure through internships. In conclusion, to fully support students' entrepreneurial aspirations, Politeknik Pariwisata Makassar must address these gaps, equipping students with the necessary skills to succeed in the competitive culinary industry.